Determination of Earthquake Magnitudes Using Duration of High-Frequency Energy Radiation and Maximum Displacement Amplitudes: Application to the April 25, 2015 Nepal Earthquake - Hara, Tatsuhiko (Kathmandu University Journal of Science Engineering and Technology, 2015)
N/A